Migrant Parents of Adolescents With School Refusal: A Qualitative Study of Parental Distress and Cultural Barriers in Access to Care - Rosenthal, Lucie; Moro, Marie Rose; Benoit, Laelia (Frontiers in Psychiatry, 2020)
Introduction: School refusal is an important problem in adolescent psychiatry. However, little is known about the experience of school refusal among minority youth (migrants and minority ethnic groups). This study assesses how parents of various cultural backgrounds experience their adolescents’ school refusal. Method: This qualitative study is based on interviews of 11 parents of teenagers diagnosed with school refusal at three adolescent outpatient mental health units in Paris and its suburbs. Interpretative phenomenological analysis was used for the thematic investigation. Results: The analysis found four themes: (i) confronting school and school refusal distresses parental representations; (ii) school refusal as a failure of the family's obligation to succeed after migration; (iii) representations of school that fluctuate with time since arrival: idealization, followed by mistrust and disappointment in the inequalities, even the racism; (iv) solutions envisioned for school refusal, confronting the healthcare system, stigma, and, again, inequality. Conclusion: All parents question their parenting choices when their children become school refusers. However, when families belong to minority groups, school refusal calls into question parents’ relations with the French school system and their immigration choices. At the same time, the construction of a multicultural identity for children and adolescents in transcultural situations requires them to strike a balance between two worlds, and school refusal endangers this delicate negotiation. Subsequent misunderstandings can lead clinicians to misdiagnose school refusal as truancy. Clinicians must take the parents' culture and migration history into account to minimize the risk of complete failure of treatment for school refusal and the ensuing inequality of care and opportunity that can result.